Scabies – frequent dermatosis, difficult diagnosis - Żelazny, Izabela; Nowicki, Roman; Sobjanek, Michał (Przewodnik Lekarza/Guide for GPs, 2007)
Scabies is a frequent interhuman ectoparasitic infection caused by a mite, Sarcoptes scabiei. It affects people of all ages, regardless of their socioeconomic status. Usually it results in a papular, intensely pruritic eruption involving the interdigital spaces and flexure creases. Although the global prevalence of this parasite is not known, it has been estimated that despite the availability of effective treatments over 300 million people are infested. Also in Poland the prevalence of scabies is increasing. Especially so-called clean man’s scabies is an epidemiological problem. There is also renewed appreciation of the role of this parasite in the causation of skin sepsis and subsequent post-infectious complications. This article summarizes the knowledge about the infestation and treatments method available.